Carmen de fundatione, ruina et restauratione inclyti monasterii gemmeticensis - Pierre Bouet (Tabularia)
The Carmen de fundatione, ruina et restauratione inclyti monasterii Gemmeticensis is a poem of 185 verses which has survived in three manuscripts: two from the XVIIth century (Paris, BnF, ms lat. 12778, p. 153-155 and Paris, BnF, ms Baluze n˚ 58, p. 174-176 v) and one from the beginning of the XVIIIth century (Paris, BnF, ms fr. 4899, p. 261-266). The poem, in dactylic hexameters, describes the foundation of the abbey of Jumièges by Abbot Philibert, its destruction by the vikings, and its restoration by Duke William Longsword in 940.According to the XVIIIth-century manuscript the poem had been engraved on copper plates at the cloister’s entry. As the cloister had been rebuilt c. 1530 by Abbot Francois de Fontenay and decorated with frescoes illustrating the main occasions in the monastery’s history, it is likely that the poem was written at that time in order to faciliate the interpretation of the painings on the cloister walls. Rather than it being a poem of the Xth or beginning of the XIth century, as it has been traditionally dated, it is more likely to be a literary exercise from the middle of the XVIth century as is shown by certain linguistic indications.